Using blogs as a tool to facilitate students’ reflection - Sithaletchemy S Krishnaiyer; Raja Hanani Raja Mushahar; Nuretna Asurah Ahmad (Penerbit UKM, 2012)
In this age of computer mediated technology, blogs for reflective journal writing have been introduced as an integral component in many courses in universities. In keeping with this trend in using blogs for reflection, first year law undergraduates who are required to take a course in English for Law had to write a reflective journal to allow students to reflect on their learning and record their responses to what they have learnt. This paper was based on an action research study to investigate the extent to which blog writing facilitates students’ reflection and the effectiveness of teacher input to enhance their reflection. Both quantitative and qualitative methods were employed to collect data. Two questionnaires were used to collect data on students’ response and experience on blog writing to facilitate reflection and effectiveness of teacher input. Blog postings were also collected and analysed for instances of reflection. The findings indicated that blog writing enhances and facilitates students’ reflection and that introducing a model of reflection enhanced the quality of reflection in students’ entries to a great extent. Blogs have proven to be useful platforms for students to reflect on their learning although students need much guidance on how to better structure their reflections.